2018
DOI: 10.4025/jphyseduc.v29i1.2946
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Amplitude De Movimento Da Coluna Torácica E Lombar: Revisão Sistemática Com Metanálise

Abstract: A coluna vertebral apresenta mobilidade e características distintas conforme a região anatômica, e, há diversos instrumentos que propiciam sua avaliação. Esta revisão sistemática objetivou identificar os métodos e instrumentos utilizados para avaliar a amplitude de movimento da coluna vertebral torácica e lombar no plano sagital que apresentam validade e/ou repetibilidade e/ou reprodutibilidade confirmados, evidenciando seus respectivos índices psicométricos. Foram realizadas buscas nas bases de dados BIREME, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, X-rays pose a health risk to patients from the exposure to ionizing radiation, and frequent use is not recommended for clinical follow-up [10,11]. In a recent systematic review, Valle, Schmit, Sedrez and Candotti [12] investigated alternative methods to assess spinal flexibility. However, only the tape measure in the modified Schoeber test, 3D videogrammetry and the Flexicurve exhibited scientific evidence supporting their repeatability and/or reproducibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, X-rays pose a health risk to patients from the exposure to ionizing radiation, and frequent use is not recommended for clinical follow-up [10,11]. In a recent systematic review, Valle, Schmit, Sedrez and Candotti [12] investigated alternative methods to assess spinal flexibility. However, only the tape measure in the modified Schoeber test, 3D videogrammetry and the Flexicurve exhibited scientific evidence supporting their repeatability and/or reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the adequate intraand interrater reproducibility obtained [17,18], this instrument is used only to assess ROM in the lumbar region, restricting its application, since it has not been tested in the thoracic spine. Moreover, a recent systematic review found only two studies that tested the validity of the Flexicurve, both with low methodological quality [12]. Thus, the aim of this study was to evaluate the concurrent validity of the Flexicurve using 3D videogrammetry as reference to assess thoracic and lumbar spine flexion and extension.…”
Section: Introductionmentioning
confidence: 99%